2015
DOI: 10.7717/peerj.1183
|View full text |Cite
|
Sign up to set email alerts
|

A survey of HK, HPt, and RR domains and their organization in two-component systems and phosphorelay proteins of organisms with fully sequenced genomes

Abstract: Two Component Systems and Phosphorelays (TCS/PR) are environmental signal transduction cascades in prokaryotes and, less frequently, in eukaryotes. The internal domain organization of proteins and the topology of TCS/PR cascades play an important role in shaping the responses of the circuits. It is thus important to maintain updated censuses of TCS/PR proteins in order to identify the various topologies used by nature and enable a systematic study of the dynamics associated with those topologies. To create suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 82 publications
(111 reference statements)
0
25
0
Order By: Relevance
“…To address this question we used a comprehensive census of PR circuit architectures, and analyzed over 9000 fully sequenced microbial and plant genomes. We found that more than 72% of all PR coded in a single operon have the same circuit architecture (M3 of Figure 1) 16 . Four additional architectures account for another 27% of all other PR (architectures M1, M2, M2', an M4 of Figure 1) 16 .…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…To address this question we used a comprehensive census of PR circuit architectures, and analyzed over 9000 fully sequenced microbial and plant genomes. We found that more than 72% of all PR coded in a single operon have the same circuit architecture (M3 of Figure 1) 16 . Four additional architectures account for another 27% of all other PR (architectures M1, M2, M2', an M4 of Figure 1) 16 .…”
Section: Introductionmentioning
confidence: 78%
“…In the case of PR, a specific architecture is observed in over 72% of all genomic PR 16 in a sample of more than 9000 organisms 4 . This suggested that indeed there could be design principles for selecting the architecture of these circuits.…”
Section: Discussion Implicationsmentioning
confidence: 99%
See 3 more Smart Citations